Low-dose aspirin is not effective as an adjunct treatment for HIV infection among people living with HIV on dolutegravir-based antiretroviral therapy: A randomised double-blind, parallel-group placebo-controlled trial - Tosi M. Mwakyandile; Grace A. Shayo; Philip G. Sasi; Peter P. Kunambi; Ferdinand M. Mugusi; Godfrey Barabona; Takamasa Ueno; Eligius F. Lyamuya (PLoS ONE, 2025)
Background Despite virologic suppression with antiretroviral therapy (ART), immune activation (IA) in people living with HIV (PLHIV) remains high and is linked to non-AIDS complications. Alongside its other virologic and immunologic benefits, aspirin promisingly appears to lower the residual IA in PLHIV in small studies. Methods We conducted a double-blind, parallel-group randomised trial involving ART-naïve PLHIV initiating ART at recruitment. Participants were randomly assigned (1:1) to receive 75 mg aspirin or placebo daily for 24 weeks, alongside standard of care. The primary outcome was proportion of participants attaining HIV viral load < 50 RNA copies/mL at weeks 8, 12 and 24. Secondary outcomes assessed at 12 and 24 weeks were CD4 count, platelet and monocyte activation (soluble P-selectin and soluble CD14, respectively), T-cell activation (CD69 expression, CD38/HLA-DR co-expression) and T-cell exhaustion (PD-1 expression). Data were analysed by intention-to-treat strategy. Between-treatment arm comparisons were made by regression models using generalised estimating equations. Competing risk analyses were employed for morbidity, all-cause mortality and adverse events (AE). Results Out of 430 recruited participants, 216 were randomised to aspirin and 214 to placebo arms, with 112 and 131 participants completing the study, respectively. Proportions of participants attaining primary outcome at week 24 were comparable (78.4% aspirin arm versus 80.67% placebo arm, p = 0.53). There was larger decrease in CD8+CD69+ (%) at 12 weeks only in the placebo arm (median change (IQR): −0.42 (−2.07, 0.33) versus −0.06 (−1.30, 0.90) in the aspirin arm, p = 0.04). Other markers and secondary outcomes: morbidity (35.6% versus 34.5%), mortality (4.63 versus 3.27 per 100 person-weeks) and AEs (96.7% versus 98.0%) were similar between the aspirin and placebo arms, respectively, p > 0.05. Conclusions Low-dose aspirin initiated alongside ART through 24 weeks did not impact virologic or immunologic markers among PLHIV. Trial registration PACTR202003522049711, NCT05525156